The application of antimicrobial photodynamic inactivation on methicillin-resistant S. aureus and ESBL-producing K. pneumoniae using porphyrin photosensitizer in combination with silver nanoparticles - Malá, Zuzana; Žárská, Ludmila; Bajgar, Robert; Bogdanová, Kateřina; Kolář, Milan; Panáček, Aleš; Binder, Svatopluk; Kolářová, Hana (Photodiagnosis and photodynamic therapy, 2021)
As resistance of bacterial strains to antibiotics is a major problem, there is a need to look for alternative treatments. One option is antimicrobial photodynamic inactivation (aPDI). The pathogenic cells are targeted by a nontoxic photosensitizer while the surrounding healthy tissue is relatively unaffected. The photosensitizer is activated by light of t appropriate wavelength resulting in the generation of reactive oxygen species that are cytotoxic for the pathogens. In this work, the photosensitizer TMPyP and silver nanoparticles (AgNPs) were investigated for their synergistic antibacterial effect. We tested these two substances on two bacterial strains, methicillin-resistant Staphylococcus aureus 4591 (MRSA) and extended-spectrum beta-lactamases-producing Klebsiella pneumoniae 2486 (ESBL-KP), to compare their effectiveness. The bacteria were first incubated with TMPyP for 45 min or 5 h, then irradiated with a LED source with the total fluence of 10 or 20 J/cm2 and then placed in a microbiological growth medium supplemented with AgNPs. To accomplish the synergistic effect, the optimal combination of TMPyP and AgNPs was estimated as 1.56-25 μM for TMPyP and 3.38 mg/l for AgNPs in case of MRSA and 1.56-50 μM for TMPyP and 3.38 mg/l for AgNPs in case of ESBL-KP at 45 min incubation with TMPyP and fluence of 10 J/cm2. Longer incubation and/or longer irradiation led to a decrease in the maximum values of the photosensitizer concentration to produce the synergistic effect. From this work it can be concluded that the combination of antimicrobial photodynamic inactivation with a treatment including silver nanoparticles could be a promising approach to treat bacterial infection.
Keywords: fotosenzibilizující látky; Methicillin Resistance; Methicillin-resistant Staphylococcus aureus (MRSA); Photosensitizing Agents; rezistence na methicilin; Klebsiella pneumoniae; Anti-Infective Agents; Methicillin-Resistant Staphylococcus aureus; antiinfekční látky; fotochemoterapie; antibakteriální látky; Silver; kovové nanočástice; Antimicrobial photodynamic inactivation (aPDI); Klebsiella pneumoniae (ESBL-KP); Silver nanoparticles (AgNPs); methicilin rezistentní Staphylococcus aureus; Porphyrins; Anti-Bacterial Agents; Synergistic effect; stříbro; Photochemotherapy; porfyriny; Extended-spectrum beta-lactamases-producing; Photosensitizer (PS); Metal Nanoparticles